Subject of Law: Three Hypostases - Grzegorczyk (author), Christophe; Ninidze (translator), Tevdore; Sumbatashvili (translator), Ekaterine (Journal of Law, 2024)
The article, the Georgian translation of which is offered to the reader, was first published in 1989 in the 34th volume of the "Archives of Legal Philosophy" magazine...